2007
DOI: 10.1136/gut.2006.093195
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy of adult liver allograft recipients in the UK

Abstract: Overall, female recipients have a longer life expectancy and lose fewer life years than male recipients. While younger recipients have a longer life expectancy, they also lose more life years. Those transplanted for cancer, hepatitis C virus infection, and alcoholic liver disease had the greatest loss of life years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 11 publications
4
42
1
2
Order By: Relevance
“…This study provides further evidence that late mortality is not improving in liver transplant recipients (1,2). The death rate after 1 year in this cohort of UK transplant recipients did not improve with time and was more than twice the unadjusted death rate in the United Kingdom A Cox regression analysis demonstrated that donor age, recipient age, recipient gender, and cause of liver disease were not significant confounding variables for survival according to era of transplantation.…”
Section: Discussionmentioning
confidence: 70%
“…This study provides further evidence that late mortality is not improving in liver transplant recipients (1,2). The death rate after 1 year in this cohort of UK transplant recipients did not improve with time and was more than twice the unadjusted death rate in the United Kingdom A Cox regression analysis demonstrated that donor age, recipient age, recipient gender, and cause of liver disease were not significant confounding variables for survival according to era of transplantation.…”
Section: Discussionmentioning
confidence: 70%
“…3 Although a recent study reported an overall life expectancy of 22.2 years for adult LT recipients, the true ceiling for patient survival and allograft longevity in children who have undergone LT remains unknown and is likely higher. 4,5 Thus, the focus of post-LT care in children has shifted to encompass consequences related to the post-transplant course. Current knowledge dictating lifelong treatment with immunosuppressive medications has particular impact for pediatric patients, given that many children will live long enough to potentially develop end-organ damage.…”
mentioning
confidence: 99%
“…Liver transplantation is an effective treatment for patients with end-stage disease, giving an average of 17-22 years of additional life [2,3] . Access to liver transplantation is limited by donor availability; several innovations, including split liver, living donor transplantation, non-heart beating donation (NHBD) and the expansion of the donor criteria, have been attempted to tackle this disparity [4] .…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%